2017
DOI: 10.1038/sc.2016.192
|View full text |Cite
|
Sign up to set email alerts
|

Outcome comparison of different approaches to self-intermittent catheterization in neurogenic patients: a systematic review

Abstract: The present review demonstrated advantages of hydrophilic-coated catheters in decreasing risk of UTI and urethral trauma as well as improving patient's satisfaction. Prelubricated catheters has been shown to be superior to conventional polyvinyl chloride catheters. Randomized controlled trials comparing hydrophilic and prelubricated catheters must be conducted to assess possible superiority and cost-effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 53 publications
1
32
0
Order By: Relevance
“…Hydrophilic and gel‐coated disposable catheters can contribute to reducing the rate of UTI (Giannantoni et al ., ; DeRidder et al ., ; Cardenas and Hoffman, ; Sarica et al ., ; Cardenas et al ., ; Chartier‐Kastler and Denys, ; Shamout et al ., ).
General principles of UTI prophylaxis: ‐ Control of the bladder's storage function (low‐pressure storage phase) ‐ Adequate IC technique ‐ Individually optimized catheter material in sufficient quantity (D'Hondt and Everaert, ) ‐ Sufficient diuresis, that is, a fluid intake of approximately 1·5 L/day (e.g.
…”
Section: Urinary Tract Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrophilic and gel‐coated disposable catheters can contribute to reducing the rate of UTI (Giannantoni et al ., ; DeRidder et al ., ; Cardenas and Hoffman, ; Sarica et al ., ; Cardenas et al ., ; Chartier‐Kastler and Denys, ; Shamout et al ., ).
General principles of UTI prophylaxis: ‐ Control of the bladder's storage function (low‐pressure storage phase) ‐ Adequate IC technique ‐ Individually optimized catheter material in sufficient quantity (D'Hondt and Everaert, ) ‐ Sufficient diuresis, that is, a fluid intake of approximately 1·5 L/day (e.g.
…”
Section: Urinary Tract Infectionsmentioning
confidence: 99%
“…Hydrophilic and gel-coated disposable catheters can contribute to reducing the rate of UTI (Giannantoni et al, 2001;DeRidder et al, 2005;Cardenas and Hoffman, 2009;Sarica et al, 2010;Cardenas et al, 2011;Chartier-Kastler and Denys, 2011;Shamout et al, 2017).…”
Section: Urinary Tract Infectionsmentioning
confidence: 99%
“…A recent systematic review by Shamout et al reported on benefits of hydrophilic‐coated catheters in terms of patient's satisfaction, QoL and complication rate, particularly in patients with spinal cord injury. However, the vast majority of included studies observed spinal cord injury patients only and reports on MS patients are rare.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, the sterile technique of intermittent self-catheterization as initially proposed by Guttmann and Frankel 14 significantly reduces prevalence of UTI and bacteriuria compared to the clean technique described by Lapides et al 5 However, it has not yet been established whether or not the incidence of UTI, other complications and user satisfaction are affected by either sterile, aseptic or clean intermittent catheterization, by coated or uncoated catheters or by any other strategy. 15 A recent systematic review by Shamout et al 16 reported on benefits of hydrophilic-coated catheters in terms of patient's satisfaction, QoL and complication rate, particularly in patients with spinal cord injury. However, the vast majority of included studies observed spinal cord injury patients only and reports on MS patients are rare.…”
Section: Findings In the Context Of Existing Evidencementioning
confidence: 99%
“…expression was also found to be elevated in NDO patients [83,84]. Again, treatment with resiniferatoxin or BoNT/A intradetrusor injections was able to reduce TRPV1 expression in those patients responding also clinically to treatment [79,83,84] Despite their promising effects in human studies, the evidence for intravesical treatment with vanilloids such as capsaicin and resiniferatoxin is still very limited and adverse events including pelvic pain, facial flush, worsening of incontinence, autonomic dysreflexia, urinary tract infection, and haematuria are very frequent [85]. Intravesical vanilloids are not approved for treatment in LUTD / LUTS and have largely fallen into oblivion, particularly after the propagation of BoNT/A intradetrusor injections.…”
mentioning
confidence: 99%